Researching the improbable: is there a recipe to “unboil” an egg? - Mendoza Paredes, Erick (2015)
Professor Tom Yuan and his team were awarded the Ig-Nobel Prize in Chemistry 2015 for creating a recipe to “unboil” an egg. Although it may seem unimportant, this work has crucial importance, as it offers the possibility of refolding denatured proteins and getting them back to its natural state. This research might have an impact on industry, as it could prevent the loss of billions of dollars.